Batidão: um estudo da variação discursiva na música funk - Orlando Junior, João (2009)
This research work has the purpose of stimulating the understanding of a musical movement that has been gaining space in the communication media, whether due to its content, connected to organized crime, whether for its theme of extreme sexual content. The funk music is a typical carioca phenomenon currently passing through a process of decriminalization and nationalization, and tries to establish itself as an artistic and cultural movement of Brazil. The corpora of the research are composed by about 300 lyrics of funk, of which 4 were selected for analysis, considering the following criteria: variation of the theme and likelihood, in case of the proibidão funk (forbidden gang funk from Rio de Janeiro). Our observations are led in the sense of examining the texts, making it feasible the introduction of an analysis model whose fundamental theory is the Analysis of the Speech. We will use, above all, the analysis instruments developed by Dominique Maingueneau, besides the recent contributions of Patrick Charaudeau and other theoreticians who enhance the studies on Speech and the linguistic variation. The results of our analysis demonstrated the presence of a discursive variation and a specificity also varied, not due to the theme, but to the diverse modes of enunciative subjectivities diffused in the discursive practices of the funk music